JUMPING ABILITIES IN FEMALE ELITE VOLLEYBALL PLAYERS: COMPARATIVE ANALYSIS AMONG AGE CATEGORIES - Krzysztof Buśko; Radosław Michalski; Joanna Mazur; Jan Gajewski (Termedia Publishing House, 2012)
The aim of the study was to examine age-related differences in the maximal power and height of rise of the body's centre of mass, measured in the counter-movement jump (CMJ) and the spike jump (SPJ), between elite cadet, junior and senior female volleyball players. The study was conducted on elite cadet (n=39), junior (n=8) and senior (n=23) female volleyball players. The maximal power and height of jumps were measured for CMJ and SPJ. Cadets had a significantly smaller maximal relative power output (40.92±8.10 W · kg-1) than junior (49.47±6.47 W · kg-1) and senior (46.70±8.95 W · kg-1) volleyball players during SPJ. The height of rise of the centre of mass measured in CMJ and SPJ were similar between groups. Our research has shown that age-related differences were observed only in power output of SPJ. The differences between elite cadet, junior and senior female volleyball players were not statistically significant in relation to height of jumps (both CMJ and SPJ), and maximal power in CMJ.